Syntheses and biological evaluation of 99mTc-HYNIC-fatty acid complexes for myocardial imaging. Issue 113 (2nd November 2015) - Mathur, Anupam; Sharma, Abhishek K.; Murhekar, V. V.; Mallia, Madhava B.; Pawade, Shital; Sarma, H. D.; Chaudhari, Pradip; Sachdev, S. S.; Banerjee, Sharmila
Abstract : The aim of the present study is to identify a 99m Tc-labeled fatty acid tracer which could be a possible substitute of the widely used 123 I-labeled fatty acids in studying myocardial metabolism and in detection of myocardial abnormalities. Abstract : The aim of the present study is to identify a 99m Tc-labeled fatty acid tracer which could be a possible substitute of the widely used 123 I-labeled fatty acids in studying myocardial metabolism and in detection of myocardial abnormalities in high-risk patients. The relevance of the study stems from the fact that in terms of wider applicability, a 99m Tc-tracer is expected to be more advantageous compared to that of a 123 I-based one. Two fatty acid (FA)-hydrazinopyridine-3-carboxylic acid (HYNIC) conjugates (11C-FA-HYNIC and 12C-FA-HYNIC) were synthesized and radiolabeled with 99m Tc using two different co-ligands system viz. tricine/ethylenediamine diacetic acid (EDDA), and tricine/trisodium triphenylphosphine-3, 3′, 3′′-trisulfonate (TPPTS), to yield four radiolabeled complexes. While all four 99m Tc-HYNIC-complexes showed uptake in the myocardium, 12C-FA-HYNIC- 99m Tc-EDDA complex showed higher uptake and retention in myocardium compared to other complexes. In general, uptake of the 99m Tc-complexes in non-target organs was lower than that of 125 I-iodophenyl pentadecanoic acid (IPPA). The 12C-FA-HYNIC- 99m Tc-EDDA complex, additionally exhibited lower liver accumulation compared to that of 125 I-IPPA. Though these features were favorable for cardiac imaging, the heart-to-blood ratio of the complexes were low (<1). Nevertheless, a dynamic SPECT image of 12C-FA-HYNIC- 99m Tc-EDDA complex in Swiss mouse showed delineation of its myocardium from proximal non-target organs. The results merit further screening of synthetically modified 99m Tc-HYNIC fatty acids for myocardial imaging.